Arah Baru Pesantren di Indonesia: Fundamentalisme, Modernisme dan Moderatisme - Badrus Samsul Fata (UIN Sunan Kalijaga Yogyakarta, 2014)
For a decade, acts of terrorism in Indonesia indicated that alumnae of pesantrens, the first three linked to Jamaah Islamiyyah (Pesantren al-Mukmin Ngruki, Pesantren Al- Muttaqien, and Pesantren Darusy Syahadah in Central Java) and the later not associated to Jamaah Islamiyyah (Pesantren al-Manar and al-Hikmah), have been proven their active involvements in such acts. The question comes up in mind is whether Pesantren has turned its function from peaceful Islamic institutions into institutions that tolerate and even outbreak violence in the name of religion. This paper is aimed to measure and portrait current developments of radical pesantrens, especially to the extent of the global Islamic political movements contributed to fuel radicalization and fundamentalism in the current situation.